Married women's participation in household decision-making. - Bantigue, Aleli (1992.)
This study was undertaken to identify the areas of household decision-making where married women of nuclear families participate. The variables involved in this study were educational attainment of women, their income, and the different areas of household decision-making. The primary instrument used in this study was an interview schedule to gather necessary data. The barangay ofMat-y, Miagao was choosen as the research site. The respondents of the study are 59 married women of nuclear familiess as 50 sample. Simple random sampling method was employed. The chi-square test was utilized primarily in data analysis to determine the presence of relationship between variables. More so, simple frequency and percentage counts were employed to make the presentation of results comprehensible. With the use of frequency and percentages, it was found out that married women are involved in every areas of decision-making in the householdd, namely financial-eonomic and socio-moral concerns. In financial-economic areas, women are more involved most particularly in household budgeting of evryday expenses. In socio-moral concerns, they are most involved specifically in the care of children. Likewise, the results of the chi-square test showed that no relationship is evident between educational attainment aand women's involvement in the decision-making process in both financial-economic and socio-moral related areas. Furthermore, as to income as the other variable, two decision-areas were found to be affected by income. Theses were under the financial-economic related aspects of decision-making specifically in borrowing of money and paying of loans or credits. Moreover, the other decision-areas tested showed no relationship between income and women's participation in the decision-making process.
Thesis (Undergraduate, Bachelor of Arts in Sociology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Women, married -- Decision-making.